Amyloid β-Protein Precursor-Rich Platelet Microparticles in Thrombotic Disease - Nomura, Shosaku; Komiyama, Yutaka; Miyake, Tetsuya; Miyazaki, Yasuhiko; Kido, Hirofumi; Suzuki, Masahiko; Kagawa, Hideo; Yanabu, Mutsumasa; Takahashi, Hakuo; Fukuhara, Shirou (Thrombosis and Haemostasis, 1994)
We investigated the association of amyloid β-protein precursor (APP) and platelet derived microparticles in 20 normal controls and 91 patients with various diseases causing a thrombotic tendency. Compared with the controls, the mean percentage of APP-positive microparticles was significantly greater in the patients with cerebral infarction (39.1 ± 17.7%, p <0.001), diabetes (31.1 ± 12.6%, p <0.001), and uremia (30.1 ± 14.7%, p <0.01), but not in those with hypertension (8.2 ±6.3%, p = NS). Sixteen patients with cerebral infarction, 20 with diabetes, and 11 with uremia had microparticles with very high APP levels. In normal controls, 7.2 ± 3.7% of the microparticles were positive for P-selectin, while the percentage in cerebral infarction, diabetes, uremia, and hypertension was respectively 43.5 ± 15.1%, 40.0 ± 12.8%, 31.8 ±12.2%, and 11.6 ±7.3%. There was a significant correlation between P-selectin and APP positivity of microparticles. Our results suggest that microparticle APP may have a regulatory influence on coagulation abnormalities.